Angiogenic potential of early and late outgrowth endothelial progenitor cells is dependent on the time of emergence. (1st May 2015) - Minami, Yoshiyasu; Nakajima, Toshiaki; Ikutomi, Masayasu; Morita, Toshihiro; Komuro, Issei; Sata, Masataka; Sahara, Makoto
Abstract: Background: Recent studies have suggested that late-outgrowth endothelial progenitor cells (EPCs) derived from human peripheral blood mononuclear cells (hPBMNCs) might have higher angiogenic potential than classically-defined early-outgrowth EPCs (EOCs). However, it still remains unclear which of "so-called" EPC subpopulations defined in a variety of ways has the highest angiogenic potential. Methods and results: We classified hPBMNC-derived EPC subpopulations by the time of their emergence in culture. EOCs were defined as attached cells on culture days 3–7. Late-outgrowth EPCs, defined as the cell forming colonies with cobblestone appearance since day 10, were further classified as follows: "moderate"-outgrowth EPCs (MOCs) emerging on days 10–16, "late"-outgrowth EPCs (LOCs) on days 17–23, and "very late"-outgrowth EPCs (VOCs) on days 24–30. Flow cytometry analyses showed the clear differences of hematopoietic/endothelial markers between EOC (CD31 + VE-cadherin − CD34 − CD14 + CD45 + ) and LOC (CD31 + VE-cadherin + CD34 + CD14 − CD45 − ). We found that LOCs had the highest proliferation and tube formation capabilities in vitro along with the highest expression of angiogenic genes including KDR and eNOS. To investigate the in vivo therapeutic efficacies, each EPC subpopulation was intravenously transplanted into immunocompromised mice (total 4 × 10 5 cells) after unilateral hindlimb ischemia surgery. The LOC-treated mice exhibited significantly-enhanced blood flow recovery (flow ratios of ischemic/non-ischemic leg: 0.99 ± 0.02 [LOC group] versus 0.67 ± 0.07 to 0.78 ± 0.09 [other groups]; P  < 0.05) and augmented capillary collateral formation in ischemic leg, which were attributable to their direct engraftment into host angiogenic vessels (approximately 10%) and paracrine effects. Conclusion: hPBMNC-derived late-outgrowth EPCs emerging on culture days 17–23 are superior to other EPC subpopulations with regard to therapeutic angiogenic potential.